The evolving energy budget of experimental faults within continental crust: Insights from in situ dynamic X-ray microtomography. (June 2019) - McBeck, Jessica; Cordonnier, Benoit; Mair, Karen; Renard, François
Abstract: We investigate the evolving distribution of strain produced by a sliding fault within intact crystalline rock, and the energetics of deformation that occur both on- and off-fault. We slid precut faults of differing roughness oriented at 45° to σ 1 while acquiring in situ X-ray microtomograms. Digital volume correlation of tomograms provide estimates of the 3D displacement and strain fields. This characterization of the strain tensor field reveal that the differing fault roughness produced distinct slip behavior, degree of strain localization and accumulation, and energy budget partitioning. The rougher fault slipped more episodically, hosted a wider and more asymmetric damage zone, and accommodated less normal and shear strain. This fault consumed more energy in off-fault deformation ( W int ) per volume and more energy in frictional slip ( W fric ) as portions of the total energy input to the system ( W ext ) than the smoother fault. In both experiments, W fric consumed the largest portion of the energy budget (50–100%), while W int consumed smaller percentages (5–20%). Tracking the temporal variability of energy partitioning revealed how evolving fault architecture determined the energetic dominance of particular deformational processes, and so highlighted the importance of tracking energy partitioning through time. Highlights: We calculate the energy budget throughout experiments with sliding precut fault. Frictional work consumes 50–100% of the energy budget. Internal work consumes 5–20% of the energy budget. Greater fault roughness increases the episodicity of slip. Greater fault roughness increases the width and asymmetry of the damage zone.